Answer:
4) [tex](x-1)^2 + (y - 1)^2 = 2[/tex]
Step-by-step explanation:
4) We can convert this polar equation to rectangular form using the following formulas:
- [tex]r^2 = x^2 + y^2[/tex]
- [tex]r \sin(\theta) = y[/tex]
- [tex]r\cos(\theta) = x[/tex]
- [tex]\tan(\theta) = \dfrac{y}{x}[/tex]
We need to manipulate the equation so some of the terms match these formulas.
[tex]r=2\cos(\theta) + 2\sin(\theta)[/tex]
↓ dividing both sides by [tex]2[/tex]
[tex]r / 2=\cos(\theta) + \sin(\theta)[/tex]
↓ multiplying both sides by [tex]r[/tex]
[tex]\dfrac{r^2}{2}=r\cos(\theta) + r\sin(\theta)[/tex]
Now, we can apply the polar conversion formulas to get the equation:
[tex]\dfrac{x^2 + y^2}{2}=x + y[/tex]
This can be manipulated to get a circle standard form equation.
↓ multiplying both sides by 2
[tex]x^2 + y^2=2x + 2y[/tex]
↓ completing the square for [tex]x[/tex]
↓ moving the x's to one side
[tex]x^2 -2x=-y^2 + 2y[/tex]
↓ adding (-2/2)², or 1, to both sides
[tex]x^2 -2x + 1=-y^2 + 2y + 1[/tex]
↓ factoring the perfect square
[tex](x-1)^2=-y^2 + 2y + 1[/tex]
↓ completing the square for [tex]y[/tex]
↓ factoring a (-1) out of the right side
[tex](x-1)^2=-1(y^2 - 2y - 1)[/tex]
↓ adding (-1)(+2) to both sides
[tex](x-1)^2 - 2=-1(y^2 - 2y - 1 + 2)[/tex]
↓ simplifying
[tex](x-1)^2 - 2=-1(y^2 - 2y + 1)[/tex]
↓ factoring the perfect square
[tex](x-1)^2 - 2=-(y - 1)^2[/tex]
↓ adding [tex](y-1)^2[/tex] to both sides
[tex](x-1)^2 + (y - 1)^2 - 2 = 0[/tex]
↓ adding 2 to both sides
[tex]\boxed{(x-1)^2 + (y - 1)^2 = 2}[/tex]